Association Between Self-Perceived Stigma and Quality of Life Among Urban Chinese Older Adults: The Moderating Role of Attitude Toward Own Aging and Traditionality - Sun, Tao; Zhang, Shu-E; Yan, Meng-yao; Lian, Ting-hui; Yu, Yi-qi; Yin, Hong-yan; Zhao, Chen-xi; Wang, Yan-ping; Chang, Xiao; Ji, Ke-yu; Cheng, Si-yu; Wang, Xiao-he; et al. (Frontiers in Public Health, 2022)
Abstract Background Ageism is a global challenge, which leads to a range of adverse outcomes among elderly people worldwide. However, how self-perceived ageism influences the quality of life in a sample of urban older adults remains inconclusive. Objectives The current study aims to assess the status of self-perceived stigma among urban Chinese older adults, identify its relationship with quality of life, and further explore whether both attitude toward own aging and traditionality moderate this relationship. Materials and Methods Primary data were collected through cross-sectional surveys among urban older adults in three provinces of China from October 2019 to December 2020. A total of 764 urban older adults were valid participants (effective response rate = 81.28%) and completed questionnaires via anonymous face-to-face interviews. Socio-demographic factors, self-perceived stigma, attitude toward own aging, traditionality, and quality of life were assessed using questionnaires that included the Self-perceived Stigma, Attitude Toward Own Ageing, Traditionality, and SF-8 Scales. Results For urban Chinese older adults, the average score of self-perceived stigma was 2.041±0.726. Self-perceived stigma (β=-0.391, P<0.05) and attitude toward own aging (β=-0.211, P<0.05) both influenced quality of life. Additionally, attitude toward own aging (β=-0.530, P<0.05) and traditionality (β=-0.525, P<0.05) moderated the association between self-perceived stigma and quality of life. Simple slope analysis revealed that when the level of negative attitude toward own aging and traditionality was higher, the strength of the influence of self-perceived stigma on quality of life was stronger. Conclusion Urban Chinese older adults were aware of the self-perceived stigma, which contributes to decreased quality of life. Attitude toward own aging and traditionality could moderate the association between self-perceived stigma and quality of life. When negative attitudes toward own aging and traditionality are higher, self-perceived stigma has a greater effect on the quality of life. More interventions related to relieving self-perceived stigma, traditionality, and negative attitude toward own aging should be considered to build a new modern society that emphasizes health, friendliness, well-being, and dignity for all ages.